How university and vocational studies can assist in reducing road traffic injuries - Darabi Golshani, Ali Mohammed; Nikraz, Hamid; Nikravan, Z. (International Association of Technology, Education and Development (IATED), 2010)
According to the World Health Organisation (WHO), every day more than 3000 people die on the world’s roads. Tens of millions of people are injured and disabled every year. It is important that good practices relating to road traffic are promoted such as the importance of seat-belt wearing, drink driving, speeding and fatigue. According to WHO’s prediction, in 2030 road traffic injuries will rise to become the fifth leading cause of death in comparison of being ninth back in 2004.WHO states the following alarming fact regarding Road Safety: Fact 1: More than 1.2 million people die in road traffic crashes every year. Fact 2: As many as 50 million people are injured or disabled by road traffic crashes every year. Fact 3: Half of all crash victims are vulnerable road users such as pedestrians, cyclists, and motorcyclists. Fact 4: Road traffic crashes cost countries up to 4% of their Gross National Product. Fact 5: Correctly used seat-belts reduce the risk of death in a crash by 61%. Fact 6: Mandatory use of child restraints can reduce child deaths by 35%. Fact 7: Helmets reduce fatal and serious head injuries by up to 45%. Fact 8: Enforcing a drinking and driving law around the world could reduce alcoholrelated crashes by 20%. Fact 9: For every 1km/h reduction in average speed, there is a 2% reduction in the number of crashes. Fact 10: Simple low-cost engineering measures are saving thousands of lives.These facts and figures are astonishing and it is vital that measures are introduced to tackle road traffic safety. One alternative method that has not been widely incorporated in today’s society that could successfully work towards tackling road traffic safety is the implementation of road safety education in Universities and Vocational institutions. The introduction of a new road safety and traffic accident prevention unit in our curriculum or the incorporation of these issues within an existing unit is required. This will enable students to think strategically and critically and take into consideration road safety and traffic prevention issues. Such units will also assist the students in developing a number of skills such as critical thinking, effective communication, self promotion and the ability to work as part of a team. Using e-learning platforms such as Blackboard could also assist us further to deliver these units in a more interactive and collaborative manner. This paper would examine road safety issues and ways they could be incorporated into a unit at the university and vocational levels.